2019
DOI: 10.3847/1538-4357/ab55d6
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Four Apparently Cold Dusty Galaxies at z = 3.62–5.85 in the COSMOS Field: Direct Evidence of Cosmic Microwave Background Impact on High-redshift Galaxy Observables

Abstract: We report Atacama Large Millimetre Array (ALMA) observations of four high-redshift dusty star-forming galaxy candidates selected from far-Infrared (FIR)/submm observations in the COSMOS field. We securely detect all galaxies in the continuum and spectroscopically confirm them at z=3.62-5.85 using ALMA 3mm line scans, detecting multiple CO and/or [CI] transitions. This includes the most distant dusty galaxy currently known in the COSMOS field, ID85001929 at z=5.847. These redshifts are lower than we had expect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
111
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 114 publications
15
111
2
Order By: Relevance
“…j Values obtained by fitting the de-blended fluxes at 100 μm-3 mm using a method virtually identical to that adopted for GN10. The T dust is compatible with the value of 61±8 K reported by Jin et al (2019). k Blended with a lower-z source that contributes ∼30% of the flux at 870 μm and likely a higher fraction at 500 μm.…”
Section: Co Large Velocity Gradient Modelingsupporting
confidence: 86%
See 2 more Smart Citations
“…j Values obtained by fitting the de-blended fluxes at 100 μm-3 mm using a method virtually identical to that adopted for GN10. The T dust is compatible with the value of 61±8 K reported by Jin et al (2019). k Blended with a lower-z source that contributes ∼30% of the flux at 870 μm and likely a higher fraction at 500 μm.…”
Section: Co Large Velocity Gradient Modelingsupporting
confidence: 86%
“…Adopting the measured CO(J=1→0) luminosity instead of that inferred from the LVG modeling would yield a ratio of ;5400 for GN10.52 We caution that a direct comparison in terms of physical properties to lower redshifts (as is typically done with photon dominated region models calculated at z=0) is not straight forward due to the reduction in the intensity of low-J CO line emission at z>5 due to the warmer CMB.53 Note that an optically thin fitting procedure suggests a more modest dust temperature of (53±5) K compared to the general fitting result adopted here, but it also yields a worse fit to the data.54 Jin et al (2019) report ID 20010161, a source with a candidate redshift of z=5.051 based on a single emission line. While the identification is plausible, we do not include it in the current data compilation until the redshift is confirmed.55 Uncertainties are given as the median absolute deviation.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…At z > 4, most of our constraints come from redshifted ultraviolet (UV) light, which probes the unobscured star formation rate (SFR). Except for a few very bright objects (e.g., Walter et al 2012;Riechers et al 2013;Watson et al 2015;Capak et al 2015;Strandet et al 2017;Zavala et al 2018;Jin et al 2019;Casey et al 2019), we have much less information about dust-obscured star formation, that is, the UV light absorbed by dust and re-emitted in the far infrared. To accurately measure the star formation history in the Universe, we need to know both the obscured and unobscured parts (e.g., Madau & Dickinson 2014;Maniyar et al 2018).…”
Section: Introductionmentioning
confidence: 96%
“…For instance, Simpson et al (2014) found ten SMGs which were detected at 3.6 µm, but not detected at shorter wavelengths. While obtaining a spectroscopic redshift of these types of near-infrared-dark SMGs is still not easy, A&A 640, L8 (2020) a handful of these galaxies are now placed at z ∼ 4−5 via molecular and atomic line detections at (sub)millimeter wavelengths and the number is increasing (e.g., Swinbank et al 2012;Riechers et al 2017;Oteo et al 2018;Casey et al 2019;Jin et al 2019;Jiménez-Andrade et al 2020;Riechers et al 2020).…”
Section: Introductionmentioning
confidence: 99%